2014
DOI: 10.1063/1.4865367
|View full text |Cite
|
Sign up to set email alerts
|

Radiation sources with planar wire arrays and planar foils for inertial confinement fusion and high energy density physics research

Abstract: International audienceThis article reports on the joint success of two independent lines of research, each of them being a multi-year international effort. One of these is the development of innovative sources, such as planar wire arrays (PWAs). PWAs turned out to be a prolific radiator, which act mainly as a resistor, even though the physical mechanism of efficient magnetic energy conversion into radiation still remains unclear. We review the results of our extensive studies of PWAs. We also report the new re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Experiments on the Zebra generator at standard current of 1 MA have demonstrated that planar wire arrays (PWA) are very efficient radiators and in particular muti-planar wire arrays can be very useful in studying radiation from two different wire materials in space and time [4]. Experiments on the Zebra generator with LCM (Load Current Multiplier, provides 1.5-1.7 MA) allow for implosions of larger sized wire array loads including PWAs than at standard current of 1 MA as well as new applications such as to ICF [5]. In this work modified multi-planar wire arrays are tested that consisted of two outer wire planes, each 4.9 mm width that were made of eight mid-atomic-number (Alumel with 95% of Ni) wires with the inter-row gap increased from 3 or 6 mm (usually used at 1 MA current) up to 9 mm.…”
Section: Motivation Experimental Details and Resultsmentioning
confidence: 99%
“…Experiments on the Zebra generator at standard current of 1 MA have demonstrated that planar wire arrays (PWA) are very efficient radiators and in particular muti-planar wire arrays can be very useful in studying radiation from two different wire materials in space and time [4]. Experiments on the Zebra generator with LCM (Load Current Multiplier, provides 1.5-1.7 MA) allow for implosions of larger sized wire array loads including PWAs than at standard current of 1 MA as well as new applications such as to ICF [5]. In this work modified multi-planar wire arrays are tested that consisted of two outer wire planes, each 4.9 mm width that were made of eight mid-atomic-number (Alumel with 95% of Ni) wires with the inter-row gap increased from 3 or 6 mm (usually used at 1 MA current) up to 9 mm.…”
Section: Motivation Experimental Details and Resultsmentioning
confidence: 99%
“…We mitigated the risk of arcs forming at this magnetic null by removing the central part of the cathode (see FIG.1a and FIG. 2a) [4]. Driven in parallel, PWA sources showed synchronized sub-keV (>0.2 keV) x-ray bursts with nearly equal amplitudes (FIG.…”
Section: Demonstration Of Equally Redistributed Currents and The Syncmentioning
confidence: 99%
“…Our UNR group, together with A. Chuvatin (and support from the SNL), designed and used the 100 ns LCM (increased Zebra current I from 0.9 to 1.7 MA) [11]. The two innovative approaches mentioned in the beginning were used in combination to produce a new concept of compact hohlraum radiation source for ICF [1] and yielded the first experimental results with simplified hohlraum design at Zebra/LCM in coordination with B. Jones, M. Cuneo and R. Vesey from the SNL [4]. The new proposed hohlraum concept is based on application of parallel-driven PWAs placed in compact cavities around central hohlraum cavity with capsule/target in the middle [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations